2020
DOI: 10.1111/apm.13076
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of analytical accuracy of HER2 status in patients with breast cancer

Abstract: Human epidermal growth factor receptor 2 (HER2) gene status and overexpression, occurring in~13.6% of primary breast cancers, is essential for identifying patients likely to benefit from biological treatment. In this method of evaluation study, we tested and compared the HER2 gene-protein assay (GPA) with routine HER2 immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH). The GPA was evaluated using 67 formalin-fixed paraffin-embedded (FFPE) HER2 equivoval IHC (2+) breast cancer tissue sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…At present, Immunohistochemistry (IHC) and fluorescence in situ hybridization (Fluorescence in situ) are the main techniques recommended by the US Food and Drug Administration for Her2 gene detection. Many studies have confirmed that there are two kinds of hybridization and FISH [6][7][8]. Although the two detection methods have good consistency in the detection of Her2 gene status, for PA-TIENTS with IHC (2+), further detection by FISH is more beneficial to obtain more accurate gene status information.…”
Section: Introductionmentioning
confidence: 99%
“…At present, Immunohistochemistry (IHC) and fluorescence in situ hybridization (Fluorescence in situ) are the main techniques recommended by the US Food and Drug Administration for Her2 gene detection. Many studies have confirmed that there are two kinds of hybridization and FISH [6][7][8]. Although the two detection methods have good consistency in the detection of Her2 gene status, for PA-TIENTS with IHC (2+), further detection by FISH is more beneficial to obtain more accurate gene status information.…”
Section: Introductionmentioning
confidence: 99%
“…According to the American Society of Clinical Oncology (ASCO)/College of American Pathologists (CAP) criteria, if the HER-2/CEP17 ratio is ≥2.0 or the HER-2 gene copy number is ≥6, the test result is considered HER-2 positive. (Jensen et al, 2020). As an effective method, combined chemotherapy with trastuzumab has become a standard treatment for HER-2 overexpressing breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the post-analytical phase, inter-observer variability can occur due to the lack of consistent epithelial internal positive control for HER2 in non-neoplastic breast tissue ( Sajjadi et al, 2022 ; Zhang et al, 2022 ). The subjective mode of HER2 assessment and HER2 intratumoral heterogeneity in HER2-low breast cancer are other barriers with great influence on HER2-low assessment ( Bianchi et al, 2015 ; Jensen et al, 2020 ; Zhang et al, 2020 ). To determine the suitability of the current standard HER2 IHC assays for identifying patients with HER2-low breast cancers, a concordance survey of 18 pathologists reading 170 breast cancer biopsies was carried out ( Fernandez et al, 2022 ).…”
Section: Current Challenges: How Far From the Perfect Test?mentioning
confidence: 99%